1983
DOI: 10.1002/ar.1092050107
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor delays the development of the epidermis and hair follicles of mice during growth of the first coat

Abstract: The structure of the epidermis and hair-follicle bulbs and the proliferative activities of their component cells were studied in the midside skin of male mice treated with epidermal growth factor (EGF) or saline during formation of the first coat (days 0-21). The epidermis was thickest at birth, but in control animals became progressively thinner as cell size and the number of layers of granular and cornified cells were reduced. EGF treatment from birth resulted in a thickening of the epidermis at 5 days of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…Nimierous reports describe the sensitivity of skin and hair to exogenous EGFR ligands (Moore et al 1983;Tam 1985;Barrandon and Green 1987;Vassar and Fuchs 1991). Our demonstration that EGFR transcripts are localized to the outer root sheath of hair follicles is consistent with a previous assay of receptor protein (Green et al 1984;King et al 1990).…”
Section: Discussionsupporting
confidence: 90%
“…Nimierous reports describe the sensitivity of skin and hair to exogenous EGFR ligands (Moore et al 1983;Tam 1985;Barrandon and Green 1987;Vassar and Fuchs 1991). Our demonstration that EGFR transcripts are localized to the outer root sheath of hair follicles is consistent with a previous assay of receptor protein (Green et al 1984;King et al 1990).…”
Section: Discussionsupporting
confidence: 90%
“…The present study showed that even when EGF was overexpressed, the skin histology was normal at birth. By Day 4, there was an increase in epidermal thickness but a decrease in both overall skin thickness and hair follicle diameter, consistent with earlier studies that involved the injection of EGF into newborn animals and showed an inhibitory role of EGF in skin development (2,3). It has also been shown that although EGFR is expressed continuously in the epidermis, expression in the hair follicles started a few days after birth.…”
Section: Discussionsupporting
confidence: 89%
“…However, the delay in skin development was not prolonged, and the mitotic index and thickness of the epidermis declined to that of control values a few days later. By Day 41, final hair length and diameter were not significantly reduced (3). EGF also had no effect on back skin when injected into mice with ages ranging from 12 to 20 days (2).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…These epidermal effects contrast those described for two other members of the EGF family, EGF and TGF-a, both of which induce marked keratinocyte proliferation but do not stimulate normal keratinocyte differentiation (38,39). In addition, both EGF and TGF-a inhibit the growth of hair follicles (40,41), while EGF stimulates the growth of sebaceous (42) and sweat glands (43). In contrast, rhNDF-a2 has no apparent effect on any dermal adnexa, both in the rabbit ear excisional wound model and after systemic administration to neonatal rats (Danilenko, D. M., and G. F. Pierce, unpublished data).…”
Section: Discussionmentioning
confidence: 64%